MyIndah Pharmacy Inventory Management System - Selvarathnam, Yuvadharshini; MOHD YUNUS, DR. MOHD AMIN (Applied Information Technology And Computer Science, 2025)
The MyIndah Pharmacy Inventory Management System (MI-PIMS) is a web-based solution designed to revolutionize inventory management in pharmacies. The system aims to address issues such as time-consuming manual order processing, inefficient stock tracking, and systemic delays. It includes features like real-time visibility of stock levels, automated low-inventory notifications, seamless integration with point-of-sale terminals, and comprehensive reporting tools. The goal is to enhance operational efficiency, accuracy, and customer satisfaction while easing current inventory management challenges. The project utilizes advanced technology to address problems associated with traditional inventory procedures, employing a methodical approach with structured design and exact user acceptance testing to ensure a reliable and error-free system. MI-PIMS is designed to accommodate the unique needs of various retail sectors through scalability and customization, promoting improved operational agility and performance. The project is expected to transform inventory management, ushering in a new era of accessible, accurate, and efficient inventory data management.